0035 Development of 12 poisoning and drug overdose case definitions for use with emergency department data in North Carolina. (26th April 2015) - Harmon, Katherine; Ising, Amy; Proescholdbell, Scott; Barnett, Clifton; Marshall, Steve; Waller, Anna
Abstract : Statement of purpose: The NC Division of Public Health, in collaboration with UNC Chapel Hill, is improving injury surveillance data as part of the NC Surveillance Quality Improvement (SQI) Project. The project has focused on improving emergency department (ED) data in the statewide public health surveillance system NC DETECT. Unlike statewide mortality and hospital discharge data, NC DETECT ED data are available in near real time with over 75% of ED visits assigned at least one billing code within two weeks of the visit. One task/goal of the NC SQI project was the development of 12 poisoning and drug overdose surveillance case definitions. Methods/Approach: The case definitions drew from existing definitions developed by state and national organisations; content experts in injury epidemiology, surveillance methods, and public health informatics; and end user feedback. Nine of the definitions incorporate diagnosis and/or E-codes (poisoning, unintentional poisoning, acute alcohol poisoning, drug overdose, unintentional drug overdose, opioid overdose, prescription analgesic opioid overdose, methadone overdose, and heroin overdose). Two definitions use a combination of diagnosis codes, E-codes, and keyword searches (drug overdose and heroin-related ED visits). One definition consists of only a keyword search (Narcan/naloxone). Results: The new case definitions were added to the NC DETECT web portal in summer 2014. Authorised users can access both current and historical ED data. Authorised users from local health departments can access line-listing data for their county and compare aggregate data to other counties and the state. These case definitions may be revised based on user feedback. In addition, custom-reports can be developed to address specific poisoning topics (e.g. fentanyl overdoses). Conclusions: NC DETECT ED data are vital to NC for public health surveillance. The development of 12 poisoning and drug overdose case definitions has streamlined poisoning surveillance activities. Significance and contribution to the field: Given the variation among poisoning case definitions available nationwide, the NC SQI project has developed definitions for use in NC, tested the efficacy of these definitions using ED data, and revised these definitions based on expert and user feedback. It is hoped that these definitions may inform surveillance activities in other states.